Funding Early College High School: Hold Harmless or Shared Commitment - Jack Leonard (Arizona State University, 2013)
Early college high schools are a promising but expensive pathway to college readiness. Most such schools are supported with state funds and/or grants. This descriptive case study presents an early college program, now in its fourth year in a traditional high school, in which the families, high school and community college shared the entire cost. Data from document analysis and interviews with administrators, parents and students clarified the funding plan and participant reactions. Joint ownership increased parental engagement, student academic commitment and administrator attention. The results suggest that learning to cope with the cost of college, which this program necessitated, is an important aspect of college readiness for both students and parents. The model of shared responsibility is contrasted with the "hold harmless" model of government/foundation support that relieves schools and families of the cost of early college programming. The findings and policy recommendations are applicable to LEA and SEA leaders, philanthropies and scholars in educational financial policy.